Developing Learning Activities Using an Open Approach Together with Assessment for Learning to Promote Mathematical Competencies of Ninth Grade Students - Promtrud, Akkarapon; Vibulrangson, Saifon (Journal of Education Studies, Chulalongkorn University, 2023)
The objectives of this research were to: 1) create and determine the effectiveness, 2) study the experimental results, and 3) examine opinions towards learning activities using an open approach together with assessment for learning to enhance the mathematical competencies of ninth grade students. The research process involved three stages: First, creation and effectiveness stage, which involved six learning activity plans, mathematical competencies test, which involved three situations, and analytic rubrics scoring. Second, trial stage, the research participants included 11 ninth grade students. The research instrument was an open-ended questionnaire was used in the third stage, studying opinion. The research findings indicate that: 1) the learning activities were found to be appropriate at the highest level (M = 4.64, SD = 0.45), as the effectiveness index for all competencies was greater than 0.5; 2) students demonstrated higher performance in all three phases: Phase 1 - capacity building, Phase 2 – proficiency development, and Phase 3 – competencies building, as the post-learning result was significantly higher than before the experiment at the .05 level of significance and was rated at an excellent level; and 3) the opinions toward the learning activities revealed the students had intrinsic motivation, learning teamwork, learning strategies, self-improvement, basic knowledge, and attitudes toward learning new things.